Assessment of the Phytochemical Profile, Free Radical Scavenging and Antibacterial Effects of Pilea symmeria from Mizoram, India: Therapeutic properties of Pilea symmeria - Rokhum, Lalremtluangi; Chinzah, Lalthansangi; Esther, Lalhmingliani; Vabeiryureilai, Mathipi (Iranian Journal of Pharmaceutical Sciences, 2025)
Antibacterial and free radical scavenging properties of Pilea symmeria, a traditional medicinal plant from Mizoram, India, have been examined in this study. Chloroform, ethanol, and aqueous were used to extract the plant components. Extracts were phytochemically analyzed qualitatively and quantitatively. The extracted sample were tested for their ability to scavenge 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis-(3- ethylbenzothiazoline-6-sulfonic acid) ABTS, and superoxide anion (O2•(-)) radicals. An antibacterial susceptibility test was performed against the bacterial strain Escherichia. coli, Bacillus subtilis and Klebsiella pneumoniae using disc diffusion method. The broth microdilution method determined the minimum inhibitory concentration (MIC). Plating samples from a well of MIC and above concentrations on a new agar plate determined minimum bactericidal concentration (MBC). Various phytochemicals, including terpenoids, tannins, flavonoids, cardiac glycosides, steroids, alkaloids, saponins, and phlobatannins, were present in the various extracts of P. symmeria. Phytochemical analysis by LC-MS revealed the presence of 34 major compounds having various biological activities. The most potent radical scavenger was ethanol extract, which contains the highest overall phenolic and flavonoid content with the lowest IC50 value. The various extracts also suppressed the tested organisms’ growth in a concentration-dependent manner. Therefore, our results suggested that P. symmeria extracts contain various phytochemicals with anti-radical and anti-bacterial activities and can potentially develop into novel phytomedicines.